Occurrence of Surgical Diseases and Hoof Diseases in Horses in Bukhara City and Surrounding Districts (International Journal of Scientific Trends, 2026)
This article presents the results of a monitoring study on the prevalence of hoof and tendon system pathologies in horses in the Bukhara region (Bukhara, Romitan, and Kogon districts) during 2025–2026. The incidence rate was found to range between 14.95% and 26.08%. Structural analysis revealed that aseptic serous tendovaginitis (37.04%) and laminitis (29.62%) were the most prevalent conditions. Additionally, tendon injuries and closed mechanical traumas accounted for 22.22% of cases. The findings indicate that excessive mechanical load, improper management, and unbalanced nutrition play a significant role in the development of distal limb pathologies. The study substantiates the importance of early diagnosis and the improvement of preventive measures in veterinary practice.